Narrative Writing on New Immigrant Women: Perspective on Cultural Identity and Mother-Daughter Relationship - Chen, Shu-Chuan; Fang, Chih-Hui (PAROLE: Journal of Linguistics and Education, 2018)
Three different types of narrative writings from women who have recently immigrated to Taiwan are discussed here: oral/confessional narrative, textual narrative, and documentary films. The first is the primary kind of narrative writing produced while immigrant women are still struggling with the acquirement of a new language, and relies on help from local people to deliver the new immigrants’ voice. The textual narrative illustrates the mother figures in terms of madness or absence from home; emphasizing the conflict of mother-daughter relationships. The last type of narrative writing produced by newly immigrating women are the documentary films, which are shot by themselves and attempt to demonstrate the bravery of these new immigrant spouses in defending their rights. The results of this paper show that, through the narrative writings, female immigrants from Southeast Asia in Taiwan have produced a variety of issues and topics which create a link of dialogue with Taiwanese society, and which need to be understood. What is more, the process of constructing their new identity is worth discussing as it provides a new perspective on Asian ethnic and women’s writing, and uncovers the need for more research into diasporic women―studied from the approach of displacement.